Rational Drug Design Of New Folic Acid Analogues With High Binding Affinity And Anticancer Activity - Althiabat, Mohammad Gasem Mohammad (2020)
The goal of this thesis is to design new FA analogues with higher selectivity to bind with FRα. Fifty FA-analogues with variant heterocyclic rings were designed and studied for their interaction with FRα. Docking results showed 20 out of the 50 FA-analogues showed higher binding affinity than methotrexate (MTX) and the parent folic acid (FA) towards FRα.